Book Review: Huttunen, Laura and Gerhild Perls (eds) 2023. An Anthropology of Disappearance: Politics, Intimacies and Alternative Ways of Knowing - Timothy Anderson (Suomen Antropologi)
Huttunen, Laura and Gerhild Perls (eds). An Anthropology of Disappearance: Politics, Intimacies and Alternative Ways of Knowing. Berghahn. 2023. 298 pp. ISBN: 978-1-80539-072-5 (hardcover), ISBN: 978-1-80539-364-1 (ebook).